Markers-traits association for iron toxicity tolerance in selected Indonesian rice varieties - YUDHISTIRA NUGRAHA; DWINITA W UTAMI; IDA ROSDIANTI; SINTHO WAHYUNING ARDIE; MUNIF GHULAMMAHDI; SUWARNO SUWARNO; HAJRIAL ASWIDINNOOR (Society for Indonesian Biodiversity, 2016)
Nugraha Y, Utami DW, Rosdianti I, Ardie SW, Ghulammahdi M, Suwarno, Aswidinnoor H. 2016. Markers-traits association for iron toxicity tolerance in selected Indonesian rice varieties. Biodiversitas 17: 753-763. Ferrous iron toxicity is a mineral disorder frequently occurring under flooded soils condition where rice is cultivated. Here we study identification the Single Nucleotide Polymorphism (SNPs) markers associated with iron toxicity tolerance characters. The phenotypical data was collected from exploiting of twenty-four rice genotypes that were grown under Yoshida + 0.2% agar solution with treatment of 400 mg. L-1 Fe2+ and control conditions. The same genotypes were grown in iron toxicity acute and control sites at Taman Bogo, Lampung Province, Indonesia. The Principle Component Analysis (PCA) of the phenotypic data showed that 18 rice genotypes were selected representing grouping of related characters to iron toxicity condition. The genotyping of selected genotypes was carried out using multiplexes of 384 SNPs Golden Gate IlluminaÂ© assay. We identified, TBGI380435 which located on 14.45 Mbp of chromosome 9 was associated to leaf bronzing and relative shoot weight characters in the greenhouse experiment. The marker was associated with heavy metal transport detoxification (HTDT). The results are expected to assist in locating the potential candidate genes or Fe toxicity tolerance and to allow for precise marker-assisted selection. This research will serve for rice improvement through marker-assisted breeding and genomic selection in Indonesia. Keywords: Golden gate assay, grain yield, leaf bronzing scores, principle component analysis, single nucleotide polymorphism Abbreviations: SNPs = Single Nucleotide Polymorphisms, AM = Association Mapping, LD= Linkage Disequilibrium, GG= Golden Gate Assay, NGS= Next Generation sequencing ,QTL = Quantitative Trait Loci, LBS = Leaf Bronzing Score, PCA = Principle Component Analysis, SES = Standard Evaluation System For Rice, GLM = General Linear Model, PC = Principle Component, HTDT = Heavy Metal Transport Detoxification